2x + y = -5
3x +5y = 3
to solve 2 equations simultaneously (at the same time), by elimination, the object is to get rid of one variable.
adding a negative to a positive equals zero, for example, 5y + -5y = 0.
So, to get rid of y in the above 1st equation, since the first equation has just "y" and the second equation has "5y", you multiply the first equation by -5 to get "-5y" so that the -5y added to 5y = 0,
Multiply the whole equation by -5
-5 (2x + y = -5) = -10x - 5y = 25
Now add the two equations together
-10x - 5y = 25
3x + 5y = 3
-7x + 0 = 28
-7x = 28
x = -4
substitute x = -4 in either equation and solve for your y value
do you understand this?
Thanks a lot buddy, I really appreciate all the time you put to help me with my question. Yeah thanks to your explanation I get it, thanks a lot:)
So here's how I substitute right?
2x+y = -5
2(-4)+y = -5
-8 +y = -5
Then I add 8 to both sides and get:
y = -3
Therefore the solution would be:
correct, the answer is (-4, 3)
TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...
Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...
Math - how do i simplify -9/2x^-3/2??? please help i dun need a answer necessary...
MATH Is there no one who can helpp??????? - how do i simplify -9/2x^-3/2??? ...
math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x
math - if x is not equal to negative 3/2, (2x^3-x^2-6x)/(2x+3)equals? a. x-2 b. ...
math - translate and simplify"six less than twice the sum of a number and three...
math - Which equation demonstrates the commutative property of addition? a. 2x+y...
Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...
Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...